Recent progress on exciplex-emitting OLEDs. Issue 3 (3rd July 2019) - Kim, Hwang-Beom; Kim, Jang-Joo
ABSTRACT: The thermally-activated-delayed-fluorescence (TADF) characteristics makes exciplexes being the hot subject in the organic light-emitting diode (OLED) research field. The theoretical limit for the efficiency of the conventional fluorescent OLEDs have been leaped by exploiting the triplet harvesting ability of exciplexes. Exciplexes are easily formed by blending electron donor molecules and electron acceptor molecules, which are generally hole transporting materials and electron transporting materials, respectively, resulting in easy access for employing exciplexes to OLEDs. We introduce the photo-physical characteristics of exciplexes derived from the charge-transfer characteristics and their application to OLEDs as emitters. Single exciplex-emitting OLEDs as well as exciplex emission-based white OLEDs are covered in this review.